Immunopathological syndromes: state of the art - Kudlay, Dmitry; Kozlov, Vladimir; Savchenko, Andrey A.; Simbirtsev, Andrey; Anisimova, Evgenia; Kudryavtsev, Igor; Kulpina, Anastasia; Rubinstein, Artem; Ryabkova, Varvara A.; Churilov, Leonid P.; Sirotkina, Olga; Vavilova, Tatyana; et al. (Frontiers in Medicine, 2025)
The review of the current state of knowledge on local and systemic immunopathological reactions of cellular and humoral origin, as well as the ways of their interaction, is considered in this article. This study aimed to organize, standardize, and conceptualize existing knowledge about immunopathological syndromes associated with innate immunity. It highlights syndromes linked to type I, II, and III hypersensitivity reactions, while also separately examining manifestations related to immunosuppression disorders. The review outlines how to differentiate humoral immunity syndromes based on the classes of immunoglobulins A, M, E, and the four subclasses of immunoglobulin G. Additionally, it provides a detailed analysis of complement system disorders and the mechanisms of systemic inflammatory response syndrome, as well as their role in various pathological processes. The authors advocate for a unified set of definitions for immunopathological syndromes related to adaptive immunity, aiming to develop a new concept of their pathogenesis. Currently, many definitions of these syndromes lack consensus, stemming from varying interpretations of their manifestations. The authors also propose standardized tools for assessing immunopathological syndromes, along with guidelines for staging and treatment optimization.